Recent advances in the development of multifunctional lipid-based nanoparticles for co-delivery, combination treatment strategies, and theranostics in breast and lung cancer - Loo, Yan Shan; Zahid, N. Idayu; Madheswaran, Thiagarajan; Mat Azmi, Intan Diana (Elsevier, 2022)
Cancer nanomedicines and the development of state-of-the-art multifunctional lipid-based nanoparticles (NPs) has become a fundamental resource in resolving challenging biomedical questions and physiological impediments. Since the approval of the first cancer nanomedicine by the U.S. Food and Drug Administration (FDA) in 1995, advances in smart nanomedicines have been made towards the functionalisation of NP surfaces and interiors for enhanced therapeutic effects and intratumoural distribution, and avoidance of rapid clearance and degradation occurring in vivo. The strategies include advances seen in the engineering of both lipid-based and hybrid lipid (e.g., a combination of lipidic and polymeric components) NPs for co-delivery, tumour targeting, combination therapy, and cancer theranostics. The development of multifunctional nanoplatforms is, therefore, a key concept in the amelioration of progressive and/or drug-resistant cancer cells and bypass of barriers in the delivery of anticancer molecules. Herein, we consolidate information on the recent advances in multifunctional lipid-based NPs for application in therapeutic and/or theranostic intervention of breast and lung cancer in animal models and human clinical trials. Respectively, both cancer types are among the leading cases of newly diagnosed cancer worldwide and are major contributors to cancer-related deaths in men and women. A quick overview on the challenges and promising ideas for developing safe-by-design multifunctional lipid-based cancer nanomedicines are also presented.